Is social inclusion sufficient for justice? - Drydyk, Jay (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
Before taking up those conceptual points, I will begin by proposing an unusually concrete conception of what «priority for the worst off» might mean, drawing on the conceptual framework of disaster relief. Then in section 2, after discussing the meaning of «social exclusion» (as relevant to justice), I consider similarities and differences between the «recovery» phase of disaster relief and efforts (outside the context of disaster) to reduce social exclusion. A key difference is that disaster recovery deals with regions in which social functioning has collapsed altogether, whereas combating social exclusion is concerned with restoring social participation of individuals to levels considered normal or customary for that society. In the third and fourth sections I will consider whether social justice does not require more than this relative restoration and whether, instead, it might require restoration of social participation to produce the highest capability levels sustainable for the entire population: a) given their economic and social resources at the time and b) as those resources expand over time (I call this an «egalitarian optimum»). In sections 5 and 6, I compare these results with the views of Harry Frankfurt and Martha Nussbaum on justice as sufficiency. I conclude, in section 7, with some consequences that follow from supplementing and reinforcing the ideas of social inclusion and exclusion with the idea of an egalitarian optimum.
Páginas 143-174
Keywords: Política social; Inclusión social; https://purl.org/pe-repo/ocde/ford#5.02.01